Comparative proteomics analysis of adult Haemonchus contortus isolates from Ovis ammon - Liu, Gongzhen; Liu, Qing; Han, Zhaoqing; Wang, Peikun; Li, Yanshen (Frontiers in Cellular and Infection Microbiology, 2023)
Haemonchus contortus (H. contortus) is an important parasite that causes disease that seriously endangers cattle, sheep, goat and camel ruminant animals. Here, we compared the diﬀerentially expressed proteins (DEPs) of H. contortus adult worms in three mouflon’s (Ovis ammon)Ovis ammon isolates. A total of 1299 adult worm proteins were identified, and 461 proteins were quantified, of which 82 (108), 83 (97) and 97 (86) signiﬁcantly upregulated (downregulated) DEPs were detected among pairwise comparisons (1-vs-3, 2-vs-3 and 2-vs-1). LC‒MS/MS and bioinformatics analysis indicated that these DEPs are mainly concentrated in cellular composition, molecular function, biological function, and catabolism pathways. In addition, GO classification and KEGG enrichment analyses were carried out to screen DEPs. The main biological processes involved in nucleotide, nucleotide phosphate, ribonucleotide, purine-containing compound, purine ribonucleotide, single-organism, oxoacid, organic, carboxylic, oxoacid metabolic processes and single-organism catabolic processes. The majority of KEGG pathways were found to be related to metabolic pathways, biosynthesis of secondary metabolites, biosynthesis of antibiotics, carbon metabolism and microbial metabolism in diverse environments. Moreover, we also found diﬀerences in the expression of some important or novel regulatory proteases, such as serine hydroxymethyl transferase (SHMT), dihydrolipoyl dehydrogenase (DLD) and transket pyr domain-containing protein (TKPD). In summary, label-free proteomics analysis of adult H. contortus worms displayed significant differences in three different individual isolates, which helps to improve our understanding of the growth and metabolic mechanisms of H. contortus in different individuals and relative natural environments and provides novel drug targets for the treatment of parasitic diseases.